The Memphis Meeting (CCVC) in Review 2018 - Space Perception: Connecting Testing, Training, and the World We Experience. - Dean, Mark T.; Weigel, Eric (Optometry & Visual Performance, 2019)
The most amazing meeting takes place every summer in Memphis; it is like no other. Sandy Tran, the OEP Resident Liaison in 2016, wrote an amazing review of that meeting, which should be called out here and read in order to understand the upcoming article better. In essence, the small group of 30-40 doctors, residents, and students tackles a specific topic and dissects and builds answers for three questions on that topic. What you will be reading is one doctor's (Mark Dean) interpretation of the topic and another's (Eric Weigel) notes from the meeting based on the presentations made. The neat thing about this meeting is that the topic changes every year; a new opportunity arises to explore a visual assumption or paradigm. I hope you enjoy the work product from the 2018 meeting.